1998
DOI: 10.1128/jvi.72.5.3762-3772.1998
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Secreting Coronavirus Neutralizing Antibodies into the Milk

Abstract: Ten lines of transgenic mice secreting transmissible gastroenteritis coronavirus (TGEV) neutralizing recombinant monoclonal antibodies (rMAbs) into the milk were generated. The rMAb light- and heavy-chain genes were assembled by fusing the genes encoding the variable modules of the murine MAb 6A.C3, which binds an interspecies conserved coronavirus epitope essential for virus infectivity, and a constant module from a porcine myeloma with the immunoglobulin A (IgA) isotype. The chimeric antibody led to dimer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…Sola et al (1998) demonstrated that the mouse mammary gland tissue performs the adequate posttranslational processing required for the correct assembly of antibody molecules. The secretion of neutralizing MAbs in the milk of transgenic animals could be applied to improve disease resistance in livestock and to prevent neonatal infections by a number of pathogens for which specific MAbs are available (Sola et al, 1998;Kolb et al, 2001). This approach may lead to the generation of transgenic animals providing lactogenic immunity to their progeny against pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sola et al (1998) demonstrated that the mouse mammary gland tissue performs the adequate posttranslational processing required for the correct assembly of antibody molecules. The secretion of neutralizing MAbs in the milk of transgenic animals could be applied to improve disease resistance in livestock and to prevent neonatal infections by a number of pathogens for which specific MAbs are available (Sola et al, 1998;Kolb et al, 2001). This approach may lead to the generation of transgenic animals providing lactogenic immunity to their progeny against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Transmissible gastroenteritis coronavirus (TGEV) infects enteric and respiratory tissues of newborn pigs and causes mortality close to 100% (Cavanagh, 1997;Sola et al, 1998). The rapid spread of the transmissible gastroenteritis (TGE) can be prevented only by vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…25 For instance, transgenic mice that express MAbs to coronavirus in their milk have been developed. 26,27 Because ruminant animals, such as cows, goats, and sheep, produce relatively large amounts of milk, genetically-modified members of these species could also be used to produce large quantities of therapeutic proteins, including MAbs. 28 Plants may be a potential source of recombinant proteins, including MAbs.…”
Section: New Approaches and Developmentsmentioning
confidence: 99%
“…The production of a few monoclonal antibodies in milk has been documented [30 •• ]. Mouse monoclonal antibodies, both humanized and non-humanized, that are capable of neutralizing coronavirus have been produced in mouse milk at a concentration of up to several grams per litre [40,41].…”
Section: Antibody Expression Systemsmentioning
confidence: 99%